Formation of scanner magnetic-optical characteristics in the NSC KIPT new-generation electron linac KUT-20 - Dovbnya, A.N.; Tolstoj, A.E.; Shendrik, V.A.; Semenets, T.A. (Вопросы атомной науки и техники, 2001)
In view of the requirements for the new accelerator KUT-20, results of the preoperational test-bench development of electromagnetic scanner characteristics are reported. Urgent tasks are outlined for further improvement of the whole extraction unit.